THE (IN)EFFICIENCY OF THE NATIONAL CONTROLLED PRODUCTS MANAGEMENT SYSTEM - SNGPC IN MANAGING MEDICINES SUBJECT TO SPECIAL CONTROL IN THE PHARMACEUTICAL CHAIN ​​IN BRAZIL - A CRITICAL ANALYSIS - Ferreira de Oliveira, Lincoln (Health and Society, 2024)
This course conclusion work has as its theme The National Controlled Products Management System-SNGPC and its inefficiency in real control in the pharmaceutical chain. The central proposal of the study is to critically analyze the SNGPC, a system created by the government with the aim of controlling and monitoring the movement of controlled medicines in the country, from their production to final consumption. The main objective is to highlight that, since its creation, the SNGPC has presented significant failures in managing the distribution chain of these products. These failures have important consequences, as they can lead to a lack of these medicines in some regions and an excess in others, in addition to facilitating the occurrence of illegal practices such as sale without a prescription or even diversion into trafficking. The guiding question of the research is: Did the SNGPC control the movement of medicine distributors to drugstores or was the control only for pharmaceutical retail? This question is fundamental to understanding whether system failures are concentrated at a specific point in the chain or whether they are diffuse. The methodology employed involves a comprehensive bibliographical review on the topic and also a detailed analysis of official SNGPC reports and other relevant government documents. It is hoped that this study can contribute to a better understanding of the challenges faced by the SNGPC and inspire proposals to improve its functioning, thus ensuring greater effectiveness in the control of controlled medications in the country.